Computational Modelling of the Interactions Between Polyoxometalates and Biological Systems - Gil, Adrià; Carbó, Jorge J. (Frontiers in Chemistry, 2022)
Polyoxometalates (POMs) structures have raised considerable interest for the last years in their application to biological processes and medicine. Within this area, our mini-review shows that computational modelling is an emerging tool, which can play an important role in understanding the interaction of POMs with biological systems and the mechanisms responsible of their activity, otherwise difficult to achieve experimentally. During recent years, computational studies have mainly focused on the analysis of POM binding to proteins and other systems such as lipid bilayers and nucleic acids, and on the characterization of reaction mechanisms of POMs acting as artificial metalloproteases and phosphoesterases. From early docking studies locating binding sites, molecular dynamics (MD) simulations have allowed to characterize the nature of POM···protein interactions, and to evaluate the effect of the charge, size, and shape of the POM on protein affinity, including also, the atomistic description of chaotropic character of POM anions. Although these studies rely on the interaction with proteins and nucleic acid models, the results could be extrapolated to other biomolecules such as carbohydrates, triglycerides, steroids, terpenes, etc. Combining MD simulations with quantum mechanics/molecular mechanics (QM/MM) methods and DFT calculations on cluster models, computational studies are starting to shed light on the factors governing the activity and selectivity for the hydrolysis of peptide and phosphoester bonds catalysed by POMs.